Academic writing in medicine and healthcare - Kazaryan, Airazat M.; Hagve, Martin; Augestad, Knut Magne; Nordby, Tom; Edwin, Bjørn; Ghanima, Waleed (Frontiers in Medicine, 2025)
The article highlights factors that can motivate doctors to do medical research. Various types of medical publications are presented. In addition, prerequisites that can contribute to successful publication are described. An overview of trends in research publication is given as well as an explanation of the terms discovery and innovation. The role and importance of research and scientific writing for progress in medicine and healthcare are discussed here. The connection between medical practice and research is also highlighted. Not least, the need for support from supervisors and management in the research and publication process is highlighted.